Wettability of chlorhexidine treated non-carious and caries-affected dentine - Ricci, H. A. [UNESP]; Scheffel, D. L. S. [UNESP]; Souza Costa, C. A. de [UNESP]; Santos, F. J. dos [UNESP]; Jafelicci, M. [UNESP]; Hebling, J. [UNESP] (Wiley-Blackwell, 2014)
BackgroundThe wettability of a surface is a prerequisite for adhesion and the type of dentine plays an important role in this property. This study evaluated the effect of different excipients of chlorhexidine (CHX)on sound and caries-affected dentine wettability.MethodsFlat dentine surfaces were prepared (n = 100) and artificial caries was induced in half of the sample. For each substrate, sound and caries-affected dentine, surfaces were assigned to five groups: (1) smear-covered dentine; (2) smear-free dentine saturated with water; (3) ethanol; (4) 1% CHX in water; or (5) 1% chlorhexidine in ethanol. The infected dentine was ground with 320-grit silicon carbide paper to the level of affected dentine. The smear layer was removed with acid, followed by rinsing, blot drying and the application of each solution (60seconds). Single Bond 2 was applied to each surface and contact angles were measured using a goniometer. Data were analysed by ANOVA and Student-Newman-Keuls ( = 0.05).ResultsContact angles were higher on sound dentine, regardless of the treatment. For sound and caries-affected dentine significantly higher angles were obtained on smear-covered dentine. Acid-etched dentine saturated with ethanol and ethanol/CHX resulted in significantly lower angles but only for sound dentine. Neither water and water/CHX nor ethanol and ethanol/CHX solutions differ with respect to dentine wettability.ConclusionsCaries-affected dentine wettability is higher than sound dentine, and chlorhexidine does not influence this property.
Keywords: Chlorhexidine; dentine-bonding agents; dentine; ethanol; matrix metalloproteinases; wettability